Stability studies on some substituted aminobenzoic acids - Rotich, Moses Kipngeno (Rhodes University, Faculty of Science, Department of Chemistry, 2003)
he thermal behaviour in the solid state of various substituted aminobenzoic acids (3-aminobenzoic acid (3-ABA), 4-aminobenzoic acid (4-ABA), 3-aminosalicylic acid (3-ASA), 4-aminosalicylic acid (4-ASA), and 5-aminosalicylic acid (5-ASA), as well as the "parent" benzoic acid (BA) and salicylic acid (SA) as reference substances, and possible decomposition products: 2-aminophenol (2-AP), 3-aminophenol (3-AP) and 4-aminophenol (4-AP), has been examined. The various sets of isomers studied showed considerable and interesting differences. Most sublimed well before melting, generally with an increasing rate of mass loss beyond their very different melting points. The existence of ranges of isomers allows for the comparison of their behaviour, including such aspects as melting, vaporisation, and the influence of products on the course of decomposition of initially-solid reactants. The differences in behaviour of 4-ASA and 5-ASA were the most remarkable, with 5-ASA being far more stable and apparently not decarboxylating readily, while 4-ASA sublimed at temperatures below the melting point, becoming less stable and decarboxylating in the liquid form. There is also a marked difference in the thermal behaviour of 3-ASA, as compared with 4-ASA and 5-ASA. It decarboxylated at higher temperatures (260Â°C) than 4-ASA (150Â°C). The addition of the possible decomposition products to these compounds showed faster decomposition for 4-ASA mixed with 3-AP. The sodium salts of 3-ASA and 4-ASA decarboxylate while that of 5-ASA did not. Binary mixtures of the substances listed above with beta-cyclodextrin (BCD), hydroxypropylbeta-cyclodextrin (HPBCD) and gamma-cyclodextrin (GCD) were prepared (by simple physical mixing or by kneading with a solvent) and were then examined for possible interactions using DSC, TG-FTIR, HSM, XRD and NMR. Generally, kneaded mixtures showed greater changes in thermal behaviour from that of the individual components than the physical mixtures, but changes in the physical mixtures were also significant. Comparison of the effects of the different CDs on the thermal behaviour of individual ASA isomers showed that HPBCD has the greatest interaction with 3-ASA and 5-ASA, followed by GCD, while BCD generally showed the least interactions. For 4-ASA, the effect of GCD is more marked than for 3-ASA and 5-ASA. GCD has the largest molecular cavity.
Keywords: Aminobenzoic acids; Aminobenzoic acids -- Stability; Salicylic acid